Legal protection for pedestrian victims who experience accidents in Lubuk Pakam city (study of decision number 2618/pid.sus/2021/pn lbp) - Purba, Nobel Manto; Mahzaniar, Mahzaniar (Journal of Law Science, 2024)
A traffic accident is an unexpected and unintentional event on the road involving vehicles with or without other road users that results in human casualties and/or property losses. Traffic accidents are a common problem in human life that can occur due to lack of driving awareness. The type of research used in this study is normative legal research, namely legal research that places law as a building of a normative system. The normative system in question is regarding the principles, norms, rules of laws and regulations, agreements and doctrines (teachings). The location of data collection in this study was at the Gakkum Unit of the Deli Serdang Police Traffic Unit located on Jl. Sudirman, No. 18. Lubuk Pakam, North Sumatra, Indonesia. The technique of designating an abstract word that is not manifested in objects, but can only be seen in its use through: questionnaires, interviews, observations, examinations (tests), documentation, and others. Researchers can use one or a combination of techniques depending on the problem faced or studied. The data analysis technique used in this legal research uses qualitative analysis. Based on the formulation of the problem of legal protection for victims of traffic accidents, the government provides social security for the welfare of the community. Social security includes public transportation safety guarantees and health care. One of the social security provided by the government is insurance. Obstacles in the implementation of legal protection for victims of traffic accidents in Lubuk Pakam City involve various interrelated aspects. From effective law enforcement to the provision of compensation and redress, as well as legal education and awareness, various challenges must be overcome to ensure that victims get the protection and justice they need. Based on the results of the study, it can be concluded that the use of the legal basis of Article 310 paragraph (4) of Law No. 22 of 2009 in this case is valid and in accordance with the provisions in force at the time of the accident. This provision provides a more specific legal framework for traffic accident cases compared to the general criminal provisions in the Criminal Code. The use of this legal basis ensures that sanctions are imposed in accordance with applicable regulations and are relevant to the type of violation that occurs.